The effects of simulated vision impairment on performance in football - Runswick, O. R.; Rawlinson, A.; Allen, P. M.; Sharpe, B. T.; Pocock, C.; Datson, N.; Birch, P.; Bruce, R.; Mann, D. L. (Journal of Sports Sciences, 2023)
Footballers with vision impairment (VI) are eligible to compete in the Para sport if they meet a minimum impairment criteria (MIC) based on measures of their visual acuity (VA) and/or visual field. Despite the requirements of the International Paralympic Committee Athlete Classification Code that each sport uses an evidence-based classification system, VI football continues to use a medical-based system that lacks evidence to demonstrate the relationship between impairment and performance in the sport. The aim of this study was to systematically simulate vision loss to establish the minimum level of impairment that would affect performance in futsal. Nineteen skilled sighted players completed tests of individual technical skill and anticipation performance under six levels of simulated blur that decreased both VA and contrast sensitivity (CS). VA needed to be reduced to a level of acuity that represents worse vision than that currently used for inclusion in VI football before meaningful decreases in performance were observed. CS did not have a clear effect on football performance. These findings produce the first evidence for the minimum impairment criteria in VI football and suggest a more severe degree of impairment may be required for the MIC.